Theoretical and experimental study on the selection of pure and mixed refrigerants for a power-cooling system driven by ultra-low-grade heat - Ahmad K. Sleiti (14778229) (2023)
This study theoretically and experimentally evaluates the performance of a system that combines an organic Rankine cycle (ORC) and a vapor compression cycle (VCC) driven by ultra-low-grade heat (ULGH). A systematic method is developed for the selection of pure refrigerants for the efficient performance of ORC over a temperature range between 50 °C and 100 °C. Binary and ternary mixtures are developed followed by sensitivity analyses and composition optimization to determine the optimal performance of these mixtures. Several experimental tests are conducted to ensure the operability of the system with the developed refrigerants. The results show that the use of ternary and binary mixtures enhances the performance of the system with lower GWP and ODP compared to pure refrigerants. Several mixtures are developed with energy efficiencies higher than 9 % at a heat source temperature of 75 °C. A mixture of R142b/R152a/R600 improves the energy efficiency of the system by 22.80 %, reduces the back work ratio by 19.40 % with an increase in the evaporation capacity by 13.25 %. The methodology and results presented herein will be useful in the development, design, and optimization of power and cooling systems driven by ULGH with pure and mixed refrigerants. Other Information Published in: Thermal Science and Engineering Progress License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.tsep.2023.101962